IMPLEMENTATION OF MODERN INFORMATION TECHNOLOGIES TRAINING IN THE PRACTICE OF PROFILE SCHOOL (Pedagogy of Higher and Secondary Education, 2022)
The article focuses on the organization, effectively pedagogical process in profile school through the use of modem information technologies.
Keywords: profit education; pedagogical process; information technology